Awareness and perception of digitisation by school library media specialists (2017)
Digitization is a tool for managing library resources in the 21s' century, however, school libraries are yet to embrace it in Nigeria. This paper assessed awareness and perception of digitisation by School Library Media Specialists (SLMSs) in secondary schools in Ibadan Metropolis, Oyo State, Nigeria. The concept of digitization, its process, benefits and challenges were concisely explained. One hundred and sixty-five copies of questionnaire were administered on randomly selected School library media specialists from fifteen secondary schools each from eleven local government areas of Ibadan Metropolis, ins: Akinyele local government area, Egbeda local government, Ibadan North, Ibadan North East, Ibadan North West, Ibadan South East, Ibadan South West, Ido, Lagelu, Oluyole and Ona Ara. The study established that few School Library Media Centres in government- owned secondary schools were manned by qualified SLMSs. In addition, many SLMSs were not aware of digitization concept, its purposes, processes and activities. The findings also revealed the perceived benefits and barriers to digitization in Nigeria. The study concluded that digitization is a necessary tool to manage school library resources in the 21s1 Century and made some recommendations.